1988
DOI: 10.1210/endo-122-6-2355
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Estrogens on Mouse Uterine Epidermal Growth Factor Precursor Protein and Messenger Ribonucleic Acid

Abstract: Estrogens stimulate the in vivo proliferation of epithelial cells of the mouse uterus. The cumulative evidence from several earlier studies suggests that the mitogenic effect of estrogens is mediated indirectly through a polypeptide growth factor. The primary focus of the present investigation was to determine whether an epidermal growth factor (EGF)-related polypeptide originates in the uterus of the immature or adult mouse under normal or altered estrogen status. Hybridization experiments revealed the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
107
1
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 268 publications
(118 citation statements)
references
References 44 publications
8
107
1
2
Order By: Relevance
“…Based on previous studies (5,8,9,17), we evaluated whether Cebpb and Igf1 could be mediators of E 2 -induced uterine epithelial proliferation. E 2 significantly up-regulated Cebpb at 2 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous studies (5,8,9,17), we evaluated whether Cebpb and Igf1 could be mediators of E 2 -induced uterine epithelial proliferation. E 2 significantly up-regulated Cebpb at 2 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…production of growth factors such as IGF-1 and EGF, and these growth factors induce uterine DNA synthesis (8)(9)(10)16). Igf1 knockout mice exhibited impaired uterine response to estrogen, which implicated the essential role of IGF-1 on uterine growth (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the EGF family in estrogenic effects in the female genital tract is well documented (31). Estrogens have effects on both EGF and EGFR in the uterus (32,33). The present study revealed that EGFR is found not only in association with the cell membrane but also in the cytoplasm and in nuclei of stromal cells in ER␤ Ϫ/Ϫ mice treated with E 2 ϩ P 4 .…”
Section: Discussionmentioning
confidence: 99%
“…We compared the changes in expression of ER mRNA and ER protein in the uterus and vagina of mice exposed neonatally to Tx and DES and changes in expression of ER mRNA in the ovariectomized adult mice given Tx and DES injections. We also tested the hypothesis that epidermal growth factor (EGF) acts as a mediator of estrogenic compounds (DiAugustine et al, 1988) by ER induction in newborn mouse uterine epithelium. …”
mentioning
confidence: 99%